Book Review: It's Not You, It's the Dishes: How to Minimize Conflict and Maximize Happiness in Your Relationship - Derek Lawson (Journal of Financial Therapy, 2014)
It’s Not You, It’s The Dishes brings economic principles and theory into the married life of couples. The authors simplify economics by providing fundamental concepts while removing technical jargon in a funny, yet intuitive way. Readers are introduced to the basics of comparative advantage, game theory, and eight other economic principles, all while learning lessons on how to resourcefully allocate their limited units of time, money, and energy to yield a better return on their biggest investment of their lives, their marriage. At its core, this is a self-help book aimed at married couples. Nevertheless, financial professionals and academics may benefit from reading the book, particularly because it may be beneficial helping to brainstorm potential solutions with their clients or as “homework” for client couples.
Keywords: book review; spousonomics; marital conflict; marital relationships